Formation of isomorphic Ir3+ and Ir4+ octamers and spin dimerization in the spinel CuIr2S4. - Radaelli, P; Horibe, Y; Gutmann, M; Ishibashi, H; Chen, C; Ibberson, R; Koyama, Y; Hor, Y; Kiryukhin, V; Cheong, S (2002)
Inorganic compounds with the AB2X4 spinel structure have been studied for many years, because of their unusual physical properties. The spinel crystallographic structure, first solved by Bragg in 1915, has cations occupying both tetrahedral (A) and octahedral (B) sites. Interesting physics arises when the B-site cations become mixed in valence. Magnetite (Fe3O4) is a classic and still unresolved example, where the tendency to form ordered arrays of Fe2+ and Fe3+ ions competes with the topological frustration of the B-site network. The CuIr2S4 thiospinel is another example, well known for the presence of a metal-insulator transition at 230 K with an abrupt decrease of the electrical conductivity on cooling accompanied by the loss of localized magnetic moments. Here, we report the determination of the crystallographic structure of CuIr2S4 below the metal-insulator transition. Our results indicate that CuIr2S4 undergoes a simultaneous charge-ordering and spin-dimerization transition-a rare phenomenon in three-dimensional compounds. Remarkably, the charge-ordering pattern consists of isomorphic octamers of Ir83+S24 and Ir84+S24 (as isovalent bi-capped hexagonal rings). This extraordinary arrangement leads to an elegant description of the spinel structure, but represents an increase in complexity with respect to all the known charge-ordered structures, which are typically based on stripes, slabs or chequerboard patterns.